Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Siswi SMA Negeri 3 Kendari Tahun 2023 - Febriyanti Febriyanti; Asnia Zainuddin; Lisnawaty Lisnawaty; Pardawati Pardawati (Lembaga Pengembangan Kinerja Dosen, 2023)
Anemia is a condition of the body in which the level of hemoglobin in the blood is less than normal. The prevalence rate of anemia in adolescents aged 15-24 years is 32%. According to WHO, normal hemoglobin levels for women over 15 years of age are >12.0 g/dl (>7.5 mmol). Anemia has a negative impact on the health of a teenager if it occurs continuously. The purpose of this investigation is to ascertain how the SMA 3 Kendari students' food, nutritional status, use of blood-supplement tablets, and menstrual cycle relate to the occurrence of anemia in 2023.. This type of research is a quantitative study with a cross sectional research design. The sample of this research was 94 respondents who were selected using a purposive-sampling technique and were analyzed using the chi square test. The results showed that there were 56.4% who had cases of anemia and 43.6% who were not anemic. There is a relationship between diet (p value = 0.014), nutritional status (p value = 0.012) and consumption of blood supplement tablets (p value = 0.027) There is no correlation between the menstrual cycle and anemia occurrence (p value = 0.413) and the incidence of anemia. The conclusion is that there is a relationship between diet, there is a correlation between nutritional status and the use of blood-supplement tablets with the prevalence of anemia, but not with the menstrual cycle.